Factors Influencing the Implementation of FLEGT Regulations of Vietnamese Wood Enterprises - Dinh Tien, Nguyen (VNU Journal of Science: Policy and Management Studies, 2025)
This paper analyzes factors influencing the implementation of FLEGT licensing regulations of Vietnamese wood enterprises under the VPA/FLEGT agreement between Vietnam and the EU. Vietnam has established the Vietnam Timber Legality Assurance System (VNTLAS) to manage legal timber exports. However, FLEGT licensing has not yet been officially implemented due to challenges in awareness and procedures. A survey of 155 enterprises shows that those with longer experience, higher export volumes, imported timber sources, and FSC certification are more likely to comply with FLEGT regulations. The paper recommends enhancing communication, simplifying licensing procedures, and improving domestic timber quality to promote effective FLEGT implementation, helping enterprises sustainably expand into the European market.